Exchange Rate Bands with Point Process Fundamentals - Perraudin, W. (IMF Working Papers; Working Paper ;, 1990)
This note derives closed form solutions for exchange rates in terms of fundamentals within a fully credible band exchange rate regime when the fundamentals are driven by Brownian motion and multiple point processes. The inclusion of point processes allows one to relax quite substantially the distributional assumptions about exchange rates implicit in models based on Brownian motions alone, and should therefore prove of use in empirical applications. Models with discontinuous driving processes also differ from the Brownian motion model in that monetary authorities will be obliged periodically to intervene on a large scale in discrete amounts.